1997
DOI: 10.1007/s002130050174
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical effects of amphetamine and alpha-flupenthixol on conditioned punishment and conditioned reinforcement: contrasts with midazolam

Abstract: In a test of conditioned punishment, saline-treated controls showed a moderate bias in responding away from a lever producing a response-contingent auditory conditioned stimulus (CS) that had been paired with mild footshock during training and towards a lever producing a neutral auditory CS. Systemic treatment with the indirect dopamine (DA) agonist amphetamine (0.25-1.0 mg/kg) produced a dose-dependent increase in the punishing effect of the aversive CS, whilst responding on the neutral CS lever was unchanged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 59 publications
8
45
0
2
Order By: Relevance
“…Hence, amphetamine may have increased the choice of the small reward-small punishment option by making animals hypersensitive to the punishment signal. The ability of amphetamine to enhance the influence that rewardrelated cues have on behavior is well known (Hill, 1970;Robbins, 1976), but amphetamine also potentiates the conditioned suppression of responding caused by presentation of a CS previously paired with footshock (Killcross et al, 1997). Such data support the suggestion that amphetamine could be enhancing the aversive nature of the signaled punishments in the rGT.…”
Section: Dopaminergic Modulation Of Rgt Performancesupporting
confidence: 66%
“…Hence, amphetamine may have increased the choice of the small reward-small punishment option by making animals hypersensitive to the punishment signal. The ability of amphetamine to enhance the influence that rewardrelated cues have on behavior is well known (Hill, 1970;Robbins, 1976), but amphetamine also potentiates the conditioned suppression of responding caused by presentation of a CS previously paired with footshock (Killcross et al, 1997). Such data support the suggestion that amphetamine could be enhancing the aversive nature of the signaled punishments in the rGT.…”
Section: Dopaminergic Modulation Of Rgt Performancesupporting
confidence: 66%
“…Considerable evidence supports a role for DA systems in various aspects of instrumental behavior, learning, stimulus salience, and responsiveness to the environment, but does not support the notion of a selective involvement of accumbens DA in mediating the primary appetitive motivation processes that underlie positive reinforcement . DA antagonists and accumbens DA depletions also impair performance on aversively motivated tasks involving avoidance, punishment, place aversion, and taste aversion (Salamone, 1994;Salamone et al, 1997;Killcross et al, 1997;Di Chiara, 2002;Huang and Hsiao, 2002). Accumbens DA transmission is elevated in response to both appetitive and aversive conditions (Salamone, 1994(Salamone, , 1996Salamone et al, 1997;Datla et al, 2002).…”
Section: The Dopamine (Da)/reward Hypothesis and The General Anhedonimentioning
confidence: 99%
“…We have previously demonstrated that high rates of responding under this schedule are maintained by contingent presentation of a drug-paired conditioned reinforcer, as omission of the drug cue decreased responding both before and after drug self-administration (Alderson et al, 2000;Arroyo et al, 1998). Furthermore, drugseeking after psychostimulant self-administration was increased (Arroyo et al, 1998;Pilla et al, 1999), reflecting the ability of these drugs to increase the control over behavior by conditioned reinforcers (Arroyo et al, 1998;Cador et al, 1991;Everitt et al, 2001;Killcross et al, 1997;Taylor and Robbins, 1984).…”
Section: Introductionmentioning
confidence: 95%